2024
DOI: 10.1039/d3ob01856c
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free synthesis of carbamoylated dihydroquinolinones via cascade radical annulation of cinnamamides with oxamic acids

Pallav Suman,
Kirti Tomar,
Chandra Shekhar Nishad
et al.

Abstract: We report a metal-free procedure for the sustainable synthesis of carbamoylated dihydroquinolinones via tandem addition-cyclization of carbamoyl radicals to cinnamamides. Readily accessible, non-toxic and inexpensive oxamic acids are used as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 75 publications
(25 reference statements)
0
0
0
Order By: Relevance
“…Motivated by the above success, we became interested in extending this strategy to carbamoyl radicals generated from oxamic acids. 11 The reaction of biaryl enone 1a with oxamic acid 4a was selected as the model reaction for the optimization studies (for details, see the ESI†) and we found that the oxidant K 2 S 2 O 8 in the presence of Ag 2 CO 3 in acetonitrile gave the expected phenanthrenone 5a in 92% yield (Scheme 4). Having established the suitable reaction conditions, the substrate scope was then examined with a range of biaryl enones as well as oxamic acids.…”
Section: Resultsmentioning
confidence: 99%
“…Motivated by the above success, we became interested in extending this strategy to carbamoyl radicals generated from oxamic acids. 11 The reaction of biaryl enone 1a with oxamic acid 4a was selected as the model reaction for the optimization studies (for details, see the ESI†) and we found that the oxidant K 2 S 2 O 8 in the presence of Ag 2 CO 3 in acetonitrile gave the expected phenanthrenone 5a in 92% yield (Scheme 4). Having established the suitable reaction conditions, the substrate scope was then examined with a range of biaryl enones as well as oxamic acids.…”
Section: Resultsmentioning
confidence: 99%